Pengaruh Pemberian Pakan Maggot (Hermatia illucens) yang Difermentasi terhadap Efesiensi Pakan dan Daya Cerna pada Ikan Nila (Oreochromis niloticus) - Yaqin, Nurul; Heriansah, Heriansah; Nursyahran, Nursyahran (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
Maggot is one of the local ingredients that has many benefits and many properties. Maggot is one of the feeds that is easy to make using organic waste. Fermentation is one of the applications of microbes in an effort to improve the quality of feed raw materials. The purpose of this study was to determine the effect of fermentation materials on the efficiency of tilapia (Oreochromis niloticus) feed and to determine the effect of fermented feed on digestibility in tilapia (Oreochromis niloticus). The method used in this study was experimental, where the experimental treatments were the types of feed and fermentation materials consisting of 4 combinations with 3 repetitions each, namely A (100% Maggot feed), B (Maggot 100 g fermented with 20 mL nano enzyme). C (Maggot 100 g multivariant fermentation 20 ml), D (Maggot 100 g fermented with 20 ml Lactobacillus). This research was conducted from May to July 2024 at the Moncongloe Maros Aquaculture Institute Laboratory. The results of the study showed that the highest feed utilization efficiency was in treatment B (SLS) with a value of 43.79%, followed by treatment D (yakult) with a value of 42.83% followed by treatment C (Em4) with a value of 42.38% and the lowest feed efficiency was in control treatment A (Maggot) of 34.46. Furthermore, maggot feed fermentation also had a significant effect (P <0.05) on the protein efficiency ratio in tilapia (Orerochromis niloticus).